Improving rice water productivity using alternative irrigation (case study: north of Iran) - Pourgholam-Amiji, Masoud; Liaghat, Abdolmajid; Khoshravesh, Mojtaba; Azamathulla, Hazi Mohammad (Water science & technology. Water supply, 2021)
Increasing population and the need for more food has made demands on water resources due to crop productions. One of the strategies for preventing the overuses of safe water resources for agriculture is to increase agricultural productivity by reducing the amount of irrigation water with a slight reduction or even maintaining the yields. Rice production in the northern region of Iran which is strategically and economically very important, requires irrigation management changing with traditional irrigation methods (flood irrigation). This study was conducted in the 2017–2018 crop season to investigate the effect of different irrigation management on water consumption, rice yield and water productivity in paddy field of Babolsar, Mazandaran, Iran. The experiment was performed in the field in a randomized complete block design with three replicates and four treatments in 12 plots. The treatments were TI (Traditional/flood Irrigation), and AI1, AI3 and AI5 (Alternative Irrigation one, three and five days after the disappearance of water from the soil surface, respectively). The number of yield components and the water productivity indexes were determined. The results of this study showed a significant difference (at 1% level) between irrigation treatments in terms of yield components including tiller number, Panicle length, filling percentage, and water productivity, but they did not have any significant effect on plant height and grain yield. The applied irrigation water for TI, AI1, AI3, and AI5 treatments was measured to be 7,940, 4,910, 4,090 and 3,290 m3/ha, respectively. The maximum yield (6.11 ton/ha) belonged to TI treatment and after that with the value of 6.02 ton/ha belonged to AI5 treatment with the least application of water. Rice water productivities for TI, AI1, AI3, and AI5 treatments were calculated to be 0.82, 1.05, 1.38 and 1.83 kg/m3, respectively. Therefore, alternate irrigation five days after the disappearance of surface water (AI5) was accepted to be the best irrigation practices among the other different irrigation management due to 56.07% reduction in water use and only 1.47% reduction in grain yield compared to control treatment.